-56(x+3)=-21(x+8)

Simple and best practice solution for -56(x+3)=-21(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -56(x+3)=-21(x+8) equation:


-56(x+3)=-21(x+8)

We simplify the equation to the form, which is simple to understand
-56(x+3)=-21(x+8)

Reorder the terms in parentheses
+(-56x-168)=-21*(x+8)

Remove unnecessary parentheses
-56x-168=-21+*(+x+8+)

Reorder the terms in parentheses
-56x-168=+(-21x-168)

Remove unnecessary parentheses
-56x-168=-21x-168

We move all terms containing x to the left and all other terms to the right.
-56x+21x=-168+168

We simplify left and right side of the equation.
-35x=0

We divide both sides of the equation by -35 to get x.
x=-0

See similar equations:

| -27.5-3x=1.3 | | -10+-10=0 | | (x+9)/3=6 | | 3+7x=2x+5 | | 3(3x+2)-1=8 | | y=1/7x-1 | | (1,4/1,5+0,3-0,36)*5+[1,16-0,5]= | | 1/5(5x-9)=4 | | 8b-(b+4)=11 | | -6+7= | | 2(3a+3)-3=5 | | 6(4x-5)=12 | | 15(x+17)=555 | | 10-2x=8y | | 12.5*10= | | 131/4+165/6+91/3 | | 6.5+X=2.7 | | 8=3-4(x-2) | | x^2+3lnx-14=0 | | 5/8x=9/4-3/8 | | 8-9=x-5+4 | | 6b-4b=6 | | x^2+2=2+3x | | x^2+1=25+x^2 | | 3x/-8-4x=-1 | | 0=-500x^2+10000x+100000 | | 17-3=x+5-3 | | 14-3=x+5-3 | | 18-(2x+1)=x-1 | | 3x+3=140 | | 18-(2x-1)=x-1 | | 1-x=4-2x |

Equations solver categories